ACCIDENT & EMERGENCY PERFORMANCE AND SENIOR DOCTOR INITIAL ASSESSMENT MODEL; NATIONAL DATA ANALYSIS FOR ENGLISH NHS HOSPITAL TRUSTS. Issue 12 (18th November 2016) - Abdulwahid, MA; Turner, J; Mason, S
Abstract : Objectives & Background: A number of systematic reviews of triage related interventions showed that there is a growing interest senior doctors performing initial assessment on patients. This study aimed to answer the following question: How do NHS trusts (NHSTs) with senior doctor assessment compare on key performance metrics such the percentage of patients waiting for more than four hours with their counterparts with no senior doctor initial assessment at triage? Methods: This was a retrospective study of English emergency departments (EDs) performance (routine A&E quality indicators analysis) from July 2014–June 2015 at NHST level. Trusts were divided into two main groups according to their triage practice. These were identified in a national survey of ED triage practices across England. The first model was a group of fifty NHSTs that operated senior doctor initial assessment of ambulance arrivals or walk-in patients. This was compared to fifty-seven NHSTs with EDs that did not operate senior doctor initial assessment including EDs that trialled this model in the past. Relevant statistical tests were undertaken to examine the possibility of a statistical significant difference amongst the A&E quality indicators across NHST groups. Results: Analysis of data showed that NHSTs with and the NHSTs without senior initial assessment in triage had similar performance with regard to all measured outcomes. It should be noted that the performance of NHSTs with senior doctor triage slightly improved on all measured outcomes after adjusting for confounding factors such as attendance rate. However, this was not statistically significant. Conclusion: Examining the output of the analysis and relative statistical tests, there is insufficient evidence to suggest that senior initial assessment in triage improve ED performance. Hence, the study findings do not support the use of senior initial assessment in triage.Figure 1